Overview of Adult Congenital Heart Disease and Maintainance of Optimal Function in Adult Congenital Heart Disease - James Yip (ACI (Acta Cardiologia Indonesiana), 2017)
Overview of Adult Congenital Heart Disease and Maintainance of Optimal Function in Adult Congenital Heart Disease